Corporate Social Responsibility in Sri Lanka: A National Business Systems Perspective - Anthonisz, Tiara (2008)
Due to the contextual and multidimensional nature of Corporate Social Responsibility (CSR), in order to fully understand CSR in global context, it is important to determine the drivers of and resultant nature of CSR cross-nationally. This paper contributes towards academic knowledge in this area by focusing on what shapes CSR in a particular national context, that of Sri Lanka. This paper applies Whitley's (1998) National Business Systems approach in order to assess whether the Institutional characteristics that form the Sri Lankan Business System, in turn, motivate and influence the nature of Sri Lankan CSR.